2018
DOI: 10.3934/publichealth.2018.2.144
|View full text |Cite
|
Sign up to set email alerts
|

Estimating physical activity trends among blacks in the United States through examination of four national surveys

Abstract: Physical activity is essential for overall good health and aids in the prevention and reduction of many diseases. In 2008, the U.S. Department of Health and Human Services (DHHS) issued the Physical Activity Guidelines for Americans to foster appropriate levels of physical activity at various ages of development. Despite these guidelines and the known benefit to being physically active; physical activity levels are significantly lower in Blacks, contributing to higher prevalence of poor health outcomes. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…Most AA women were from high socioeconomic status (SES) backgrounds and, therefore, our findings may be more generalizable to AA populations of similar economic status. Consistent with much of the literature, including a recent study that compiled physical activity patterns from four national datasets [54], AA women with higher education and/or income levels tend to be more physically active than their respective counterparts. It is clear that more work dedicated to understanding the factors associated with PA maintenance in AA positive outliers from lower economic backgrounds is needed.…”
Section: Discussionsupporting
confidence: 68%
“…Most AA women were from high socioeconomic status (SES) backgrounds and, therefore, our findings may be more generalizable to AA populations of similar economic status. Consistent with much of the literature, including a recent study that compiled physical activity patterns from four national datasets [54], AA women with higher education and/or income levels tend to be more physically active than their respective counterparts. It is clear that more work dedicated to understanding the factors associated with PA maintenance in AA positive outliers from lower economic backgrounds is needed.…”
Section: Discussionsupporting
confidence: 68%
“…We used accelerometers to measure MVPA and then compared levels of MVPA minutes per day to participants’ CVD risk factors. Previous studies used self‐reported physical activity to investigate relationships with CVD risk among African American adult populations 11,12,15 . In addition, all health measures were recorded on‐site by trained technicians and none of the health measures assessed in this analysis were self‐reported, decreasing the potential for social desirability or recall bias in our data.…”
Section: Discussionmentioning
confidence: 99%
“…One prior study measured physical activity using accelerometry in African American adults, but did not compare these trends with CVD risk. 15 Another study used data from the National Health and Nutrition Examination Survey that incorporates accelerometry to measure physical activity; the sample was predominantly White, however, and only a few CVD risk factors were assessed. 16 Although another previous study investigated physical activity using accelerometry in African American adolescents, 17,18 studies among African American adults are lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its benefits, AA women engage in PA at levels well below national recommendations (i.e., 150 minutes/week of moderateintensity PA, 75 minutes of vigorous PA, or an equivalent combination of durations and intensities [23,24]). Recent self-report data from three national surveys (i.e., 2015 BRFSS, 2011-2014 NHANES, and 2014 NHIS) [25] indicated that only 27% to 40% of AA met national PA guidelines. Objectively-measured PA estimates from 2003-2004 NHANES [26] and other large cohort studies (i.e., REGARDS [27] and CARDIA [28]) reflect similar trends.…”
Section: Introductionmentioning
confidence: 99%